Social Media Video Content Strategies Drive Supply Chain Brand Visibility: Strategi Konten Video Media Sosial Mendorong Visibilitas Merek Rantai Pasok - Bertrand Errent Geraldie; Yulianto Mochamad Rizal (Procedia of Social Sciences and Humanities, 2026)
General Background Modern business marketing requires adaptation to rapid digital information exchange that significantly shapes current consumer purchasing behavior. Specific Background Social media platforms, particularly those emphasizing short video content, offer highly efficient promotional channels for supply chain enterprises seeking broader audience reach. Knowledge Gap Despite this technological availability, many retail and supply chain operators still lack practical understanding regarding digital media utilization and content performance analysis. Aims This descriptive qualitative study investigates the formulation and application of video-based digital marketing strategies to build brand visibility for Al Kahfi Supply Chain. Results Observational data from TikTok analytics demonstrates that interactive product demonstrations and reseller recruitment videos generated a massive surge in total viewers, profile visits, and shares. Furthermore, demographic analysis indicates that this visual content successfully captured a specific target market, predominantly young females aged eighteen to thirty-four. Novelty The research highlights the specific utility of integrated short video metrics, such as search queries and traffic sources, as direct evaluation tools for supply chain promotional strategies. Implications Businesses must consistently utilize analytical data to refine their visual content and targeted messaging, thereby securing a stronger competitive advantage and expanding market reach within the digital economy. Highlights:  Interactive short video content significantly increases audience engagement and profile visits for supply chain enterprises. Reseller recruitment messaging combined with product demonstrations successfully captures a targeted demographic of young consumers. Analytical tools evaluating traffic sources and search queries are essential for refining digital promotional campaigns. Keywords: Digital Marketing Strategy, Social Media Promotion, Video Content Creation, Supply Chain Visibility, Audience Analytics